Human Capital, Work Culture, and Job Satisfaction Scales for Higher Education Institutions: A Bibliometric and Literature Review with Scale Development and Validation toward the Sustainable Development Goals (SDGs) - Hartono Hartono; Anidah Robani; Abdul Muhid; Reza Rachmadtullah (Bumi Publikasi Nusantara, 2026)
This study developed and validated human capital, work culture, and job satisfaction scales for higher education institutions in support of the Sustainable Development Goals (SDGs). A bibliometric and literature review was used to identify key constructs related to human resource development, organizational culture, and employee well-being in higher education. The scale development process followed an adapted model through pre-development, development, and post-development stages. The instruments were tested with 42 lecturers and educational staff working at an Indonesian university in Indonesia. Item validity and Cronbach’s Alpha reliability analyses showed that human capital, work culture, and job satisfaction items met acceptable psychometric standards. These findings indicate that validated instruments are needed to assess institutional human resources systematically. The scales can support data-driven institutional human resource development.